An Attempt to Evaluate Selected Aspects of "Bone–Fat Axis" Function in Healthy Individuals and Patients With Pancreatic Cancer. Issue 32 (August 2015) - Blogowski, Wojciech; Dolegowska, Katarzyna; Deskur, Anna; Dolegowska, Barbara; Starzyńska, Teresa; Pamela von, Reisswitz.
<x xml:space="preserve">Abstract</x> Abstract Recently, much attention has been paid to a potential biochemical cross-talk between the metabolism of the adipose tissue (AT) and bone (marrow), termed "bone–fat axis." We hypothesized that selected substances, participating in this "dialog, " are associated with body mass and peripheral trafficking of bone marrow-derived stem cells (BMSCs) in both healthy individuals and patients with obesity-associated malignancies such as pancreatic adenocarcinoma. We performed an analysis of the systemic levels of selected substances involved in the regulation of bone (marrow) homeostasis (parathormone, calcitonin, osteopontin, osteonectin, stem cell factor [SCF], and fibroblast growth factor-23) in 35 generally healthy volunteers and 35 patients with pancreatic cancer. Results were correlated with the absolute number of circulating BMSCs and body mass values. Additionally, subcutaneous and visceral/omental AT levels of the aforementioned molecules were analyzed in lean and overweight/obese individuals. Intensified steady-state trafficking of only Lin-CD45 + CD133 + hematopoietic stem/progenitor cells was observed in overweight/obese individuals and this was associated with BMI values and elevated levels of both osteonectin and SCF, which also correlated with BMI. In comparison to healthy individuals, patients with cancer had significantly higher osteopontin levels and lower values of both osteonectin and osteonectin/osteopontin ratio. While no significant correlation was observed between BMI and the number of circulating BMSCs in patients with cancer, peripheral trafficking of CD34 + KDR + CD31 + CD45-endothelial progenitor cells and CD105 + STRO-1 + CD45-mesenchymal stem cells was associated with the osteonectin/osteopontin ratio, which also correlated with BMI (r = 0.52; P < 0.05). AT levels of the examined substances were similar to those measured in the plasma, except for osteonectin, which was about 10 times lower. Our study highlights the potential role of osteonectin, osteopontin, and SCF as communication signals between the bone (marrow) and AT in both healthy individuals and patients with pancreatic cancer. We postulate that these molecules may be overlooked biochemical players linking body mass and BMSCs with obesity-associated cancer development and/or progression in humans.